Dual server-based secure data-storage system for cloud storage. (1st January 2014) - Go, Woong; Kwak, Jin
Users can access data that they store in cloud storage anytime and anywhere over a network. In the cloud storage paradigm, users' data are stored in several distributed servers and virtualisation is applied in order to logically integrate those data. However, when users access their data in cloud storage, they directly access the server on which the data are physically stored. Thus, there is a potential threat of data loss due to a malicious attacker accessing the data. In order to solve this threat, we propose a data storage system that uses link and data servers. The link server does not store real data; it only has the address of the data and a symmetric key. The data server, on the other hand, has the real data and access information, and it can only be accessed via the link server.